Stomach fish bone perforation - Rudik, N. V.; Sementsov, A. S.; Fedchuk, D. B. (Modern medical technology, 2020)
Stomach foreign bodies take second place after foreign bodies of the esophagus and can be both harmless as well as life-threatening. The shape, size, and time of the swallowed foreign body to get deposited in the specific location determine the type of treatment. The article presents a clinical observation – the stomach wall perforation of fish bones, principles of examination of the patient, computed tomography data and surgical treatment.